Crimes in the past : archaeological and anthropological evidence - Shvedchikova, Tatiana,; Moghaddam, Negahnaz,; Barone, Pier Matteo, (Archaeopress Archaeology, 2021)
This text discusses examples of crime scenes in the archaeological past, their detection and interpretation with the help of modern science; readers will find cases of historic and prehistoric 'crimes scenes' known from various contexts: (pre)historic (mass) graves, lethal violent acts related to warfare, ritual killings, or possible murder cases.